Gerdes in pictures - Tello Malpartida, Aurelio (2023)
Contains photographs of Federido Gerdes, divided into: Portrait gallery, Federico Gerdes at the National Academy of Music, Federico Gerdes in society, Federico Gerdes director and programs of presentations at the National Academy of Music, with a total of 14 images.